A Tale of Two Domains Pushing Lateral Roots. (August 2021) - Sager, Ross; Bennett, Malcolm; Lee, Jung-Youn
Abstract : Successful plant organ development depends on well-coordinated intercellular communication between the cells of the organ itself, as well as with surrounding cells. Intercellular signals often move via the symplasmic pathway using plasmodesmata. Intriguingly, brief periods of symplasmic isolation may also be necessary to promote organ differentiation and functionality. Recent findings suggest that symplasmic isolation of a subset of parental root cells and newly forming lateral root primordia (LRPs) plays a vital role in modulating lateral root development and emergence. In this opinion article we discuss how two symplasmic domains may be simultaneously established within an LRP and its overlying cells, and the significance of plasmodesmata in this process. Highlights: During some plant developmental processes, specific cells or groups of cells must become symplasmically isolated for various functions, including reaching a growth signal threshold, preventing harmful signal leakage into neighboring cells, turgor retention, and more. Lateral root formation and emergence involves the formation of at least one symplasmic domain within the new organ itself, a process which has been previously characterized. However, recent evidence points to a new potential domain in the root cells overlying the developing lateral root, cells that eventually separate to allow the new organ to grow outward. Auxin controls the spatiotemporal expression of the plasmodesmal regulator plasmodesmata-located protein (PDLP)5 in root cells overlying lateral root primordia, and PDLP5 negatively feedback regulates auxin accumulation.